Isolation of Potato X-Virus from Collecting Plants (Global Scientific Review, 2023)
This article is about obtaining a purified preparation of potato virus X with the help of biological and physicochemical methods in the presence of D. tatula plant, in which the plant was infected with the virus by mechanical inoculation and the disease symptoms were observed in 18-20 days. TSK-65 was used to obtain a purified preparation of the virus. Viral fractions began to separate from 65-69 ml, and the highest concentration of virus corresponded to fractions of 80-85 ml.